Brain gym y psicomotricidad en los niños de nivel inicial II de la Escuela de Educación Básica 18 de Noviembre de la ciudad de Loja, periodo 2022 – 2023 - Vivanco Arias, María Cristina (2023)
Psychomotricity is a discipline that helps children to develop their body and mind as a unit, whose mission is the development of the human psyche, its relationship with others and its needs through movement. It is also the set of emotional, psychomotor and cognitive interactions, which is concerned with the overall progress of the child based on his bodily experiences that facilitate the development of perception, communication and expression capacities through the active interaction of his body with the environment that surrounds him. This work is oriented to determine if the Brain Gym contributes to the strengthening of the psychomotricity of children of early level II of the School of Basic Education “18 de Noviembre” of the city of Loja, in the academic period 2022-2023. The research design was pre-experimental with a quantitative approach and a descriptive scope. The methods used for its development were: inductive, deductive, analytical-synthetic. For the initial and final diagnosis of the psychomotor profile, the scale of Evaluation of Psychomotor in the Preschool level of Victoria de la Cruz and Carmen Mazaira (EPP) was applied to twenty-four children. The results show that: 63% of the children were in a low level and only 8% in a good one. For this reason, an activity guide called "Playing and jumping the body we are exercising" was designed, once applied, a significant improvement was evidenced, achieving that: 75% of children are located at a good level and 4% at a low level. It is concluded that the Brain Gym proposal contributes to the strengthening of psychomotor skills in children of the early level, because it helps in an integral way to child development. Keywords: Brain Gym, psychomotor skills, body movement, psychomotor skills.